Tahir Jalaluddin and Syed Shaykh Al-Hadi's aptation of the Salafiyyah ideas into colonial Malaya - Zakariya, Hafiz (Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2007)
The early decades of the twentieth century witnessed the emergence of the salafi-inspired reform movements in various parts of Southeast Asia. Kiyai Haji Ahmad Dahlan and Muhammadiyah movement led such reform in Java whereas a group of refomlists, spearheaded by Haji Rasu!. Haji Abdullah Ahmad, and Shaykh Jamil Jambik carried out similar reform in West Sumatra. In colonial Malaya, the safafi-'~'(j ideas found its following among a group of concerned Muslim scholars. These ideas were brought to Malaya primarily through reform-minded students/scholars who had studied in the Middle East. and the cin:ulation of su/afiyva writings such as al-A1anfir that reached audience in Malaya. Like the safajiyya figures in the VI iddle East, the primary concern of the local reformists was the backwardness of Malay-Muslim community and the Muslim ummah at large. Against the background of Malay backwardness the reformists believe that it is imperative for them to carry out a reform campaign in their own society to redress the malady and problems confronting them. In doing so. they believed that restoration of the purity of Islamic teachings and practices are necessary for the Muslims to get out from the material slump, and intellectual stagnation.